An investigation of mental imagery in bipolar disorder: Exploring "the mind's eye". (20th December 2016) - Di Simplicio, Martina; Renner, Fritz; Blackwell, Simon E; Mitchell, Heather; Stratford, Hannah J; Watson, Peter; Myers, Nick; Nobre, Anna C; Lau‐Zhu, Alex; Holmes, Emily A
Abstract : Objectives: Mental imagery abnormalities occur across psychopathologies and are hypothesized to drive emotional difficulties in bipolar disorder (BD). A comprehensive assessment of mental imagery in BD is lacking. We aimed to test whether (i) mental imagery abnormalities (abnormalities in cognitive stages and subjective domains) occur in BD relative to non‐clinical controls; and (ii) to determine the specificity of any abnormalities in BD relative to depression and anxiety disorders. Methods: Participants included 54 subjects in the BD group (depressed/euthymic; n=27 in each subgroup), subjects with unipolar depression (n=26), subjects with anxiety disorders (n=25), and non‐clinical controls (n=27) matched for age, gender, ethnicity, education, and premorbid IQ. Experimental tasks assessed cognitive (non‐emotional) measures of mental imagery ( cognitive stages ). Questionnaires, experimental tasks, and a phenomenological interview assessed subjective domains including spontaneous imagery use, interpretation bias, and emotional mental imagery. Results: (i) Compared to non‐clinical controls, the BD combined group reported a greater impact of intrusive prospective imagery in daily life, more vivid and "real" negative images (prospective imagery task), and higher self‐involvement (picture‐word task). The BD combined group showed no clear abnormalities in cognitive stages of mental imagery. (ii) When depressed individuals with BD were compared to the depressed or anxious clinical control groups, no significant differences remained—across all groups, imagery differences were associated with affective lability and anxiety. Conclusions: Compared to non‐clinical controls, BD is characterized by abnormalities in aspects of emotional mental imagery within the context of otherwise normal cognitive aspects. When matched for depression and anxiety, these abnormalities are not specific to BD—rather, imagery may reflect a transdiagnostic marker of emotional psychopathology.